2021
DOI: 10.3389/frvir.2021.658509
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Avatar Embodiment on Time Perception - Towards VR for Time-Based Therapy

Abstract: Psycho-pathological conditions, such as depression or schizophrenia, are often accompanied by a distorted perception of time. People suffering from this conditions often report that the passage of time slows down considerably and that they are “stuck in time.” Virtual Reality (VR) could potentially help to diagnose and maybe treat such mental conditions. However, the conditions in which a VR simulation could correctly diagnose a time perception deviation are still unknown. In this paper, we present an experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 96 publications
(170 reference statements)
3
8
0
Order By: Relevance
“…However the study was limited in terms of immersion and the implementation of the virtual embodiment. Unruh et al [68] countered many of these limitations by using an HMD, replicating a real environment in VR, giving subjects a human avatar and measuring virtual embodiment using a questionnaire tailored and validated specifically for virtual embodiment. Unlike Zopf et al [90], they did not investigate an active scenario, but simply had subjects wait in VR and showed that the manipulation of virtual embodiment impacts time perception in a waiting room scenario.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However the study was limited in terms of immersion and the implementation of the virtual embodiment. Unruh et al [68] countered many of these limitations by using an HMD, replicating a real environment in VR, giving subjects a human avatar and measuring virtual embodiment using a questionnaire tailored and validated specifically for virtual embodiment. Unlike Zopf et al [90], they did not investigate an active scenario, but simply had subjects wait in VR and showed that the manipulation of virtual embodiment impacts time perception in a waiting room scenario.…”
Section: Discussionmentioning
confidence: 99%
“…All time perception items as well as our additional embodiment item, the VRSQ, the IPQ and the VEQ ratings were analyzed on the interval measurement scale [5,29,48,68].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations